2009
DOI: 10.1021/ef9005252
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Plate-Type Microreformer for Methanol Steam Reforming Reaction

Abstract: A numerical simulation is performed in this study for a plate-type microreactor with parallel microchannels and diagonal inlets/outlets. The methanol steam reforming reaction is considered, and the performance is evaluated by examining the concentration profiles of methanol, hydrogen, and carbon monoxide within the rector under various operating conditions, including the influences of the steam/carbon (S/C) ratio, reaction temperature, and liquid feed rate. Particularly, the effect of aspect ratio of the micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…The most common designs are variations of a coated wall plate reactor with zig-zag's internal fluid flow, coated wall Swiss-roll reactors, and packed bed reactors (21)(22)(23)(24)(25)(26)(27)(28) .…”
Section: Reactor Designmentioning
confidence: 99%
“…The most common designs are variations of a coated wall plate reactor with zig-zag's internal fluid flow, coated wall Swiss-roll reactors, and packed bed reactors (21)(22)(23)(24)(25)(26)(27)(28) .…”
Section: Reactor Designmentioning
confidence: 99%
“…Kumar et al [24] developed a one-dimensional nonisothermal model for an oxygen permeable membrane reactor to simulate the partial oxidation of methane to produce hydrogen. Chen et al [25] used a numerical model to analyze a plate-type reactor for methanol reforming of steam. Wang et al [26] simulated the thermal and chemical reaction performance of steam methane reforming in solar thermochemical reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Reforming reaction is not uniform in these microreformers due to uneven distribution of reactants in the channels. Microchannels in the central part of a reformer always exhibit better reforming performance [28]. Chen et al [28] found that such a plate type design of the methanol microreformer may cause non-uniform reaction rates in each microchannel and affect its reforming performance significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Microchannels in the central part of a reformer always exhibit better reforming performance [28]. Chen et al [28] found that such a plate type design of the methanol microreformer may cause non-uniform reaction rates in each microchannel and affect its reforming performance significantly. Besides this, in case of microreformers with multiple channels and multiple stacks placed one above the other, two more difficulties faced are feed stream branching with uniform flow rate for each stack and catalyst replacement after catalyst deactivation.…”
Section: Introductionmentioning
confidence: 99%